Cuidados paliativos na atenção básica: depoimentos de profissionais da saúde - Costa, Isabelle Cristinne Pinto (2011)
Palliative care are considered as a care philosophy, whose scope is to provide to patients without therapeutic possibilities of cure and their families a better quality of life, being its application of great importance in the context of Primary Care. OBJECTIVES This study has the following objectives: to investigate the understanding of professionals working in FHS, in what concerns to Palliative Care and its therapeutics modalities; to identify, in the view of professionals from FHS, the constitution of Palliative care team for Basic Attention; to verify the possibilities and limitation of implementing Palliative Care in Basic Attention; from the discourse of Health professionals. METHODOLOGY Its about and exploratory research with qualitative approach. The scenario of investigation consisted of family care units belonging to Sanitary District IV, located in the city of João Pessoa (PB). Participated in the work 30 professionals from FHS, being ten doctors, ten nurses and ten dental surgeons. Data collection occurred between July and September 2011. DATA ANALYSIS empirical material was analyzed through content analysis technique, from the following phases: pre-analysis; material exploration; treatment of results. Data obtained by means of testimonies of investigation participants were grouped into the following thematic categories: Palliative Care conceptual aspects and therapeutic modalities (with their respective subcategories: Palliative Care promotion of life quality for patients without possibilities of cure; therapeutic modalities in palliative care); Palliative Care in Basic Attention team formation, possibilities and limitations. RESULTS: This study showed, from the vision of professionals involved in the study, the valuation of Palliative Care, considered as a modality of care that aims to minimize the suffering of the patient without therapeutic possibilities of cure and the one of their families through an assistance guided in humanization. On the other side, some of the study participants had an incompatible comprehension with the relevant literature to Palliative Care. Results pointed out that doctors, nurses and dental surgeons believe in the possibility of implementing this modality of care in basic Attention, since some need are met, such as: team training and development of a national policy for palliative care. FINAL CONSIDERATIONS We consider that this study opens new horizons in the field of scientific production, in assistance and in teaching on palliative care in Basic attention. In view of reduced quantum of studies directed to the respective thematic in the context of national literature. We hope, therefore, that this research can subsidize new investigation exploring the interrelationship of Palliative Care with Basic Attention, since it is an innovative practice in the referred field, necessitating a greater spread with managers, professionals of Health, in particular the ones from FHS, students and researches from this area.